2012
DOI: 10.1158/1541-7786.mcr-11-0502
|View full text |Cite
|
Sign up to set email alerts
|

FOXA1 Is Essential for Aryl Hydrocarbon Receptor–Dependent Regulation of Cyclin G2

Abstract: The aryl hydrocarbon receptor (AHR) is a ligand-activated transcription factor that mediates the effects of the environmental contaminant 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD). Recently, AHR has emerged as a potential therapeutic target for breast cancer by virtue of its ability to modulate estrogen receptor-a (ERa) signalling and/or its ability to block cell proliferation. Our previous studies identified cyclin G2 (CCNG2), an inhibitor of cellcycle progression, as an AHR target gene; however, the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…The cell-context dependence of gene regulation by nuclear receptors is well documented and is thought to be determined by differences in cell background, in particular by differences in the contents of coregulators and other cofactors with which these receptors bind to form multicomponent complexes that regulate gene expression at the chromatin level (Lonard and O’Malley, 2012; McKenna et al, 2014; Smith and O’Malley, 2004; Stender et al, 2010). In fact, it is noteworthy that ERα and AhR interact with many of the same coregulators and cofactors, including the coregulators RIP140 (Madak-Erdogan and Katzenellenbogen, 2012), SRC 1, 2, and 3 (Endler et al, 2012; Madak-Erdogan and Katzenellenbogen, 2012) and FOXA1 (Ahmed et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…The cell-context dependence of gene regulation by nuclear receptors is well documented and is thought to be determined by differences in cell background, in particular by differences in the contents of coregulators and other cofactors with which these receptors bind to form multicomponent complexes that regulate gene expression at the chromatin level (Lonard and O’Malley, 2012; McKenna et al, 2014; Smith and O’Malley, 2004; Stender et al, 2010). In fact, it is noteworthy that ERα and AhR interact with many of the same coregulators and cofactors, including the coregulators RIP140 (Madak-Erdogan and Katzenellenbogen, 2012), SRC 1, 2, and 3 (Endler et al, 2012; Madak-Erdogan and Katzenellenbogen, 2012) and FOXA1 (Ahmed et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that CCNG2 participates in carcinogenesis and is a known tumor suppressor gene (15)(16)(17)(20)(21)(22)(23)(24)(25)(26). CCNG2 gene expression is downregulated in thyroid (20), oral (21), ovarian (22), breast (23,24), gastric (16), esophageal (17), prostate (25), kidney (26) and colorectal (15) cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline expression of a subset of genes (e.g., CCNG2, an inhibitor of cell cycle-progression [69]; Fig. S6) was altered by RAD21 depletion in the absence of estrogen, perhaps reflecting inhibition of entry into the cell cycle.…”
Section: Cohesin Depletion Modulates Transcription Of a Subset Of Estmentioning
confidence: 99%